TINDAK PIDANA YANG DIANCAM DENGAN SANKSI PIDANA MATI DALAM KITAB UNDANG-UNDANG HUKUM PIDANA - Sitti Aisyah (LPPM STIH Awang Long, 2023)
The death penalty is regulated in Law Number 1 of 2023 concerning the Criminal Code. Article 98 of the Law states that the death penalty is the most serious punishment and must always be threatened alternatively with life imprisonment or imprisonment for a maximum of 20 (twenty) years. Death penalty is a sanction carried out with a choice of lethal acts (by the state) to the perpetrators of criminal acts who have been found guilty of a court decision that has permanent legal force. Judging from the purpose of punishment, the death penalty is not essentially the main or principal means to regulate, discipline and improve individuals or society. Death penalty is only a means of exception. as far as possible the death penalty is avoided by choosing an alternative punishment in the form of life imprisonment or imprisonment for a certain time, a maximum of 20 years.